Digital Marketing Strategy and Consumer Behavior: A case study of E-Commerce Businesses - Muhammad Fatkhurohman Albashori; Sri Wahyuning; Himawan Agung Nugroho (Oikonomia : Journal of Management Economics and Accounting, 2025)
In an era of rapid technological advancement, digital marketing has emerged as an important strategy for businesses, especially in the e-commerce sector. This research investigates the relationship between digital marketing strategies and consumer behavior in e-commerce businesses. Through a case study approach, this research explores how various digital marketing tools such as social media marketing, search engine optimization (SEO), email campaigns, and influencer endorsement influence consumer decision-making, purchase intent, and brand loyalty. Data was collected through surveys and in-depth interviews with e-commerce managers and consumers. The findings reveal that personalized marketing and social media engagement significantly influence consumer trust and purchase behavior. In addition, the study highlights the importance of content quality and responsiveness in shaping consumer satisfaction and retention. This research contributes to the growing literature on digital marketing by providing practical insights for e-commerce businesses aiming to improve their marketing effectiveness and build long-term relationships with customers in a competitive digital landscape.